CFD modeling of asphaltenes deposition from crude oil through discrete phase simulations - Emani, S. (Medwell Journals, 2017)
Crude oil fouling in processing equipment have been a major unresolved problem in petroleum industries. The underlying behavior of fouling precursors present in the crude oil have to be investigated to mitigate the deposit formations. In the present research, an attempt has been made to predict the asphaltenes deposition rate from crude oil in a heat exchanger tube through discrete phase CFD simulations. Various forces such as stochastic collision, thermophoretic, Saffman lift, coalescence and drag are applied on the particles to understand the transportation and adhesion mechanism of the asphaltenes particles. As asphaltenes have the tendency to aggregate irreversibly with different particle sizes, the transportation of asphaltenes particles is studied through varying the particles diameters. The propensity of asphaltenes particles in a Lagrangian frame is studied through the available discrete phase models in the commercial CFD Software Ansys Fluent. © Medwell Journals, 2017.